2009
DOI: 10.1007/s10551-009-0027-y
|View full text |Cite
|
Sign up to set email alerts
|

Pirate or Buy? The Moderating Effect of Idolatry

Abstract: idolatry, music piracy, social identity theory, theory of planned behavior,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
48
1
2

Year Published

2011
2011
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(56 citation statements)
references
References 51 publications
(86 reference statements)
3
48
1
2
Order By: Relevance
“…Similarly, Chiou, Huang, and Lee (2005 reported that worldwide sales of recorded music fell by 7% in value and 8% in units in 2002 compared with 2001. Wang, Chen, Yang, and Farn (2009) reported that music CD sales in Taiwan during 2004 were one-third of the level in 1997. On 15 February 2012 RnBXclusive, a popular music website was shut over allegations that it offered illegal downloads that cost musicians £15million a year.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, Chiou, Huang, and Lee (2005 reported that worldwide sales of recorded music fell by 7% in value and 8% in units in 2002 compared with 2001. Wang, Chen, Yang, and Farn (2009) reported that music CD sales in Taiwan during 2004 were one-third of the level in 1997. On 15 February 2012 RnBXclusive, a popular music website was shut over allegations that it offered illegal downloads that cost musicians £15million a year.…”
Section: Introductionmentioning
confidence: 99%
“…The predictive power of attitudes has been shown to be significant in predicting a variety of normative behaviors (e.g., Anker, Feeley, & Kim, 2010;Chen & Chiu, 2009;De Groot & Steg, 2007;Hurd, Zimmerman, & Reischl, 2011), including theft intentions and behaviors (e.g., Tonglet, 2002;Cronan & Al-Rafee, 2008;Henle et al, 2010;Wang et al, 2009). However, attitudes may not always result in subsequent behavior.…”
Section: Discussionmentioning
confidence: 99%
“…Attitudes are an important predictor of moral intentions and behaviors, including a variety of prosocial and antisocial behaviors (e.g., Anker, Feeley, & Kim, 2010;Chen & Chiu, 2009;De Groot & Steg, 2007;Hurd, Zimmerman, & Reischl, 2011). Different scholars have shown that attitudes towards theft play an important role in predicting intentions and subsequently theft behaviors (e.g., Tonglet, 2002;Cronan & Al-Rafee, 2008;Wang, Chen, Yang, & Farn, 2009;Henle, Reeve, & Pitts, 2010). Therefore, examining the factors influencing attitudes towards theft can provide useful ways to decrease the occurrence of theft.…”
Section: Introductionmentioning
confidence: 99%
“…Others have relied on the theory of reasoned action and planned behavior and showed that all three core components of the modelattitudes, perceived behavioral control, and social norms -are relevant and provide a basis to explore a wide range of specific motivating factors related to digital piracy 10,32,46,47,48,49,50 . For example, research has demonstrated that Machiavellianism 47 , antipathy towards music industry 32,51 , high costs and low benefits 46 , self-efficacy 50 , anticipated guilt 52 , and idolatry 53 influence attitudes towards digital piracy.…”
Section: Psychological and Social Perspectivementioning
confidence: 99%